Pure Neuritic Leprosy In Children With Grade 2 Disability On Hands And Feet: A Rare Case And Literature Review - Gunawan H; Ruchiatan K; Puspitosari D; Hindritiani R; Usman HA; Widjaja S (International Medical Case Reports Journal)
Hendra Gunawan,1 Kartika Ruchiatan,1 Diah Puspitosari,1 Reti Hindritiani,1 Hermin Aminah Usman,2 Stephanie Widjaja1 1Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran, Dr. Hasan Sadikin Hospital, Bandung, Indonesia; 2Department of Anatomical Pathology, Faculty of Medicine, Universitas Padjadjaran, Dr. Hasan Sadikin Hospital, Bandung, IndonesiaCorrespondence: Hendra Gunawan, Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin Hospital, Jl. Pasteur 38, Bandung, West Java, 40161, Indonesia, Tel +6281221111215, Email h.gunawan2016@unpad.ac.idAbstract: Pure neuritic leprosy (PNL) is a rare clinical variant of leprosy, especially in children. This variant of leprosy only involves peripheral nerves without skin involvement or acid-fast bacilli (AFB) found on slit-skin smear examination. The challenging diagnosis and establishment of PNL due to the absence of skin lesions often lead to disability. A case of PNL with grade 2 disability of hands and feet in a 16-year-old boy was reported. The patient has been living in a leprosy-endemic area and has a history of contact with people who have symptoms of leprosy. On physical examination, there were finger contractures on both hands and feet, accompanied by bilateral ulnar, common peroneal, and posterior tibial nerve enlargement without any skin lesions. No AFB was found on the slit-skin smear examination. The diagnosis of PNL was established by the mononeuritis multiplex detected on the nerve conduction examination and the histopathological examine from the biopsy of the left ulnar nerve, which showed lymphocyte infiltration. The patient was treated with multidrug therapy for multibacillary leprosy and consulted with the Department of Physical Medicine and Rehabilitation and the Department of Orthopaedics and Traumatology for contracture management. Clinicians need to be aware of the signs and symptoms of PNL in order to avoid delays in diagnosis and treatment, as the diagnosis and establishment of PNL remain challenging.Keywords: children, grade 2 disability, nerve biopsy, nerve conduction study, pure neuritic leprosy